HUBUNGAN KELEBIHAN BERAT BADAN SELAMA MASA PANDEMI COVID-19 DENGAN PENINGKATAN RESIKO PENYAKIT JANTUNG KORONER DI RW 03 DESA SUKAMANAH JONGGOL - Nurhidayah Perwaningsih (2021)
Coronary heart disease (CHD) is the main killer in the world also Indonesia. The majority of sufferers are aged 40-60 years and the risk increased due to being overweight or obese. The Covid-19 pandemic causes limited space for movement and community activities, which can lead to weight gain. This study aims to determine the relationship of being overweight during the pandemic with an increased risk of CHD in middle adults in RW 03 Sukamanah Jonggol Village. The method used is descriptive analytic with a cross-sectional design. Samples were taken with a total sampling technique of 76 respondents. Data analysis used univariate analysis and bivariate analysis using Chi-square test. The results showed that there was a relationship between excess weight during the pandemic and the risk of CHD (p value = 0.000), there was a relationship between physical activity and CHD risk (p value = 0.000), and there was a relationship between diet and CHD risk (p value = 0.009). ). Individuals with middle adulthood who are susceptible to CHD should maintain their diet and physical activity during the pandemic so that their weight does not increase or are maintained as to reduce the risk of experiencing coronary heart disease.